2017
DOI: 10.1007/s00382-017-3783-x
|View full text |Cite
|
Sign up to set email alerts
|

Heavy rainfall in Mediterranean cyclones. Part I: contribution of deep convection and warm conveyor belt

Abstract: In this study, we provide an insight to the role of deep convection (DC) and the warm conveyor belt (WCB) as leading processes to Mediterranean cyclones' heavy rainfall. To this end, we use reanalysis data, lighting and satellite observations to quantify the relative contribution of DC and the WCB to cyclone rainfall, as well as to analyse the spatial and temporal variability of these processes with respect to the cyclone centre and life cycle. Results for the period 2005-2015 show that the relationship betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
73
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(81 citation statements)
references
References 69 publications
(88 reference statements)
6
73
2
Order By: Relevance
“…The distinction between mesoscale, slantwise ascent of the WCB and upright embedded convection had already been made in 1993 in a study on the mesoscale frontal structure of an explosively intensifying cyclone measured during the ERICA field experiment (Neiman et al, 1993). Embedded deep convection was also documented in a number of WCBs observed in the Mediterranean region (Flaounas et al, 2016;Flaounas et al, 2018) and during the North Atlantic Waveguide and Downstream Impact Experiment (NAWDEX) field campaign in the North Atlantic (Oertel et al, 2019;Blanchard et al, 2020). While slantwise WCB ascent leads to large-scale stratiform precipitation and the formation of widespread regions with low-PV air at upper levels, convective WCB ascent goes along with peaks of particularly strong surface precipitation and the formation of mesoscale upper-level PV dipoles, including regions with negative PV (Oertel et al, 2020).…”
Section: Introductionmentioning
confidence: 88%
“…The distinction between mesoscale, slantwise ascent of the WCB and upright embedded convection had already been made in 1993 in a study on the mesoscale frontal structure of an explosively intensifying cyclone measured during the ERICA field experiment (Neiman et al, 1993). Embedded deep convection was also documented in a number of WCBs observed in the Mediterranean region (Flaounas et al, 2016;Flaounas et al, 2018) and during the North Atlantic Waveguide and Downstream Impact Experiment (NAWDEX) field campaign in the North Atlantic (Oertel et al, 2019;Blanchard et al, 2020). While slantwise WCB ascent leads to large-scale stratiform precipitation and the formation of widespread regions with low-PV air at upper levels, convective WCB ascent goes along with peaks of particularly strong surface precipitation and the formation of mesoscale upper-level PV dipoles, including regions with negative PV (Oertel et al, 2020).…”
Section: Introductionmentioning
confidence: 88%
“…The WCB typically ascends poleward from the boundary layer to the upper troposphere ahead of the cyclone's cold front (Harrold, ; Browning, ; ) and plays a key role for the formation of clouds and precipitation in midlatitudes (e.g. Browning, ; Eckhardt et al ; Madonna et al ; Flaounas et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Browning, ). However, recent remote‐sensing observations (Binder, ; Crespo and Posselt, ; Flaounas et al ; ) and high‐resolution simulations (Rasp et al ) have indicated that convective activity is commonly embedded in the WCB. This concept was already proposed by Neiman et al () as the escalator–elevator mechanism, which describes the alteration between gentle slantwise frontal ascent (the escalator ) and rapid vertical motion induced by convective activity (the elevator ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies also corroborated the occurrence of convection embedded in the warm conveyor belt (WCB) airstream (Binder, 2016;Crespo and Posselt, 2016;Rasp et al, 2016;Flaounas et al, 2016Flaounas et al, , 2018Oertel et al, 2019Oertel et al, , 2020Blanchard et al, 2020) as originally proposed by Neiman et al (1993) in their so-called 'escalator-elevator' concept. In the classical perspective, the WCB (e.g.…”
Section: Introductionmentioning
confidence: 57%
“…Although recent case studies have corroborated the presence of embedded convection in WCBs (Rasp et al, 2016;Crespo and Posselt, 2016;Flaounas et al, 2016Flaounas et al, , 2018Oertel et al, 2019), several major issues are still uncertain: (i) Where and how often is convection generally embedded in the WCB ascent region? (ii) How variable is the strength of embedded convection in WCBs?…”
Section: Introductionmentioning
confidence: 99%